2009
DOI: 10.1007/s11151-009-9215-2
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implications of the Effects of Concentration and Multimarket Contact in China’s Airline Market

Abstract: Unlike many other mergers in developed countries, which might have been assessed and their effects estimated by antitrust authorities before being granted antitrust immunity, the airline mergers that swept China's airline industry in 2002 occurred with no antitrust challenge. These mergers provide the opportunity to study important market power issues in China's airline markets. Given that increased concentration and multimarket contact are the main legacies of an airline merger, the effects of mergers on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Further research with a wider scope would be required in order to draw such conclusions. Comparing our results with previous empirical work on non-European airlines such as Baum and Korn (1996;1999), Gimeno andWoo, (1996), Miller (2010), Prince and Simon (2009), Zhang and Round (2009), Bilotkach, (2011) and Singal (1996 naturally raises difficult obstacles. Indeed, beyond the fact that only Baum and Korn (1999) and our study theorized and tested a curvilinear relationship between multimarket contact and rivalry in the airline industry, other obstacles to generalization relate primarily to (1) the choice of time periods studied and differences in institutional environments, (2) stages in the competitive life cycle (3), maturity of strategic groups (4) differences in propensities to enter into alliances and (5) Competition for timeslots.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Further research with a wider scope would be required in order to draw such conclusions. Comparing our results with previous empirical work on non-European airlines such as Baum and Korn (1996;1999), Gimeno andWoo, (1996), Miller (2010), Prince and Simon (2009), Zhang and Round (2009), Bilotkach, (2011) and Singal (1996 naturally raises difficult obstacles. Indeed, beyond the fact that only Baum and Korn (1999) and our study theorized and tested a curvilinear relationship between multimarket contact and rivalry in the airline industry, other obstacles to generalization relate primarily to (1) the choice of time periods studied and differences in institutional environments, (2) stages in the competitive life cycle (3), maturity of strategic groups (4) differences in propensities to enter into alliances and (5) Competition for timeslots.…”
Section: Discussionsupporting
confidence: 73%
“…delays, etc.). In contrast, Zhang and Round (2009) Adapted from Chen (1996, p.108) multimarket contact on rivalry are observable in the context of industries other than the airlines, such as the US newspaper industry (Fu, 2003), the pharmaceutical industry (Guedri & McGuire, 2011) and the insurance industry (Greve, 2008).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Specification 1 shows that China Eastern and Air China charged significantly higher prices (about 5%) than Shanghai Airlines while China Southern and Hainan Airlines charged much lower airfares (by 7.1% and 8.4% respectively). Zhang and Round (2009) reported the aggressive pricing strategy used by Hainan Airlines to expand its domestic networks. Similar strategy might have been used here to establish reputation in this relatively new market.…”
Section: Model Estimation and Discussion Of Resultsmentioning
confidence: 99%
“…This is because most explicit and implicit price collusive agreements do not last long, as observed by Zhang and Round (2009). They found that many price-fixing agreements were actually very vulnerable and could be easily upset by a change in outside conditions such as demand.…”
Section: Model Estimation and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation